2019
DOI: 10.1155/2019/1716074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mental Fatigue on Small-World Brain Functional Network Organization

Abstract: Brain functional network has been widely applied to investigate brain function changes among different conditions and proved to be a small-world-like network. But seldom researches explore the effects of mental fatigue on the small-world brain functional network organization. In the present study, 20 healthy individuals were included to do a consecutive mental arithmetic task to induce mental fatigue, and scalp electroencephalogram (EEG) signals were recorded before and after the task. Correlations between all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…That is to say, the coexistence of small-world feature and fractal feature in the brain functional networks may be caused by neither complete attraction nor complete exclusion between central nodes. Previous researchers have reported that the small-world feature still exists in the brain functional networks when the brain is at fatigue state [ 3 , 10 , 38 ]. Taking together with the results of this study, we can infer that the small-world feature and fractal feature of the brain functional networks can still exist simultaneously during the formation of mental fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…That is to say, the coexistence of small-world feature and fractal feature in the brain functional networks may be caused by neither complete attraction nor complete exclusion between central nodes. Previous researchers have reported that the small-world feature still exists in the brain functional networks when the brain is at fatigue state [ 3 , 10 , 38 ]. Taking together with the results of this study, we can infer that the small-world feature and fractal feature of the brain functional networks can still exist simultaneously during the formation of mental fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Mental fatigue has become a widespread subhealthy condition in nowadays society [ 1 ]. Many researchers are dedicated to the studies of detection methods [ 2 ], neural mechanisms [ 3 ], and mitigation methods [ 4 ] of the mental fatigue, owing to the negative effects of mental fatigue on the human cognitive functions [ 5 ], especially serious in driving fatigue [ 6 ]. Recently, mental fatigue has been prevalently explored by the means of brain functional network with the neuroimaging technique of electroencephalogram (EEG) [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Furthermore, a large number of electrodes increases the accuracy of electrical source estimation [167] and signal preprocessing [47]. In contrast, García-Prieto et al [168], Li et al [169], and Wang et al [170] recommend fewer than 32 electrodes, demonstrating that a small number is adequate to cover the ROI and obtain reliable information. A small number is also suggested by Luck [33], indicating that the use of 16-32 active electrodes is better for monitoring brain activity.…”
Section: B) Quality Assessmentmentioning
confidence: 99%